Access to Insulin Products in Pakistan: A National Scale Cross-Sectional Survey on Prices, Availability, and Affordability - Amna Saeed; Amna Saeed; Amna Saeed; Krizzia Lambojon; Krizzia Lambojon; Krizzia Lambojon; Hamid Saeed; Zikria Saleem; Naveed Anwer; Muhammad Majid Aziz; Muhammad Majid Aziz; Muhammad Majid Aziz; et al. (Frontiers Media S.A., 2022)
Background: Diabetes is among the top ten most prevalent diseases in Pakistan, and the availability of medicines to treat the disease is vital for a great percentage of the country's population. Insulin was discovered a century ago; however, its access in several parts of the globe remains an issue. This study aims to evaluate prices, availability, and affordability (access components) of insulin and five comparator medicine access in Pakistan.Methods: A nationwide cross-sectional survey was conducted to evaluate the access to insulin and some comparator medicines in eight cities of Pakistan, using a modified WHO/HAI methodology. The survey included 80 medicine outlets, i.e., 40 private pharmacies and 40 public hospitals. Data for every unique insulin product available in the Pakistani market were obtained, including five comparator medicines. Percentage availability, median unit prices (MUPs), and affordability (the number of days' wages (NDWs) required for a month's course by the lowest-paid unskilled government worker) of all products were calculated, including originator brands (OBs) and biosimilar (BS) products.Results: Of all insulin products surveyed (n = 320), 87.5% were manufactured by foreign multinational companies (MNCs). None of the insulin products had an ideal availability of 80% in any of the surveyed health facilities. In the public sector, none of the insulin products had an availability of more than 50%. In the public sector, the overall availability of human insulin was 70% (including OB and BS). While in the private sector, the overall availability of human insulin was 90% and that of analog insulin was 62.5%. The analog insulin products were 72.8% costlier than the human insulin products. The median prices of BS insulin were 25.4% lower than the OB products, indicating that almost one-fourth of the cost could be saved by switching to BS human insulin from OB human insulin. All oral anti-diabetic medicines were found to be affordable, whereas none of the insulin was affordable. The NDWs for human and analog insulin were 1.38 and 5.06.Conclusion: In Pakistan, the insulin availability falls short of the WHO's benchmark of 80%. Insulin continues to be unaffordable in both private and government sectors. To increase insulin access, the government should optimize insulin procurement at all levels, promote local production, enforce biosimilar prescribing, and provide financial subsidies for these products.